Nomenclature changes in the mite families Neopygmephoridae and Pygmephoridae (Acari: Heterostigmata: Pygmephoroidea) with redescription of two little known species - Khaustov, Alexandr A. (Zootaxa, 2011)
The type materials of Neopygmephoridae and Pygmephoridae deposited in the Zoological Institute of Russian Academy of Sciences, St. Petersburg, Russia and the Museum of Zoology, I. Mechnikov Odessa National University, Ukraine were examined. Two genera and several species were synonymyzed. In the family Neopygmephoridae, the genus Heteropygmephrus Kurosa, 2002 syn. nov. is a junior synonym of Aegiptophorus Sevastianov and Abo-Korah, 1984 and Heteropygmephorus onthophagi Kurosa, 2002 syn. nov. is a junior synonym of Aegiptophorus shibinensis Sevastianov and AboKorah, 1984; Bakerdania uniseta Khaustov and Hajiqanbar, 2004 syn. nov. is a junior synonym of Bakerdania tenuispina Sevastianov, 1974; Bakerdania nouri Sevastianov and Zahida Al Douri, 1989 syn. nov. is a junior synonym of Bakerdania urbanensis Sevastianov, 1974; Bakerdania ptilophora Savulkina, 1978 syn. nov. is a junior synonym of Bakerdania montana (Willmann, 1956). In the family Pygmephoridae, the genus Asiapygmephorus Khaustov and Chydyrov, 2003 syn. nov. is a junior synonym of Mesopotamiophorus Sevastianov and Zahida Al Douri, 1991, and Asiapygmephorus paucisetosus (Sevastianov and Chydyrov, 1991) syn. nov. is a junior synonym of Mesopotamiophorus babylonicus Sevastianov and Zahida Al Douri, 1991; Pygmephorus scrobiculatus Sevastianov, 1975 syn. nov. is a junior synonym of Pygmephorus stammeri Krczal, 1959; Pediculaster petrovanikitinae Sevastianov, Chydyrov and Marroch, 1994 syn. nov. is a junior synonym of Pediculaster athiasae (Wicht, 1970); Pediculaster crassipedis Sevastianov and Chydyrov, 1994 syn. nov. is a junior synonym of Pediculaster amerahae Sevastianot and Abo-Korah, 1984; Pediculaster monoufiensis Sevastianov and Abo Korah, 1985 syn. nov. is a junior synonym of Pediculaster kneeboni (Wicht, 1970); Siteroptes dionusii Sevastianov and Abo-Korah, 1984 syn. nov. is a junior synonym of Siteroptes rosae Sevastianov and Abo-Korah, 1984; Siteroptes tameri Sevastianov and Abo-Korah, 1984 syn. nov. is a junior synonym of Siteroptes graminicola Mitrofanov, Shabanova and Sevastianov, 1984. Bakerdania urbanensis Sevastianov, 1974 and Neositeroptes rosae (Sevastianov and Abo-Korah, 1984) comb. nov. (transferred from Siteroptes) are redescribed.